Skin Necrosis and Purpura Fulminans in Children With and Without Thrombophilia—A Tertiary Center's Experience. (3rd October 2015) - Fruchtman, Yariv; Strauss, Tzipora; Rubinstein, Marina; Ben Harush, Miriam; Revel-Vilk, Shoshana; Kapelushmik, Joseph; Paret, Gideon; Kenet, Gili
Abstract : Purpura fulminans (PF) is a very rare clinicopathologic skin disorder comprising dermal microvascular thrombosis associated with perivascular hemorrhage of multiple origins. It may occur as the presenting symptom of severe congenital deficiency of protein C (PC) or protein S (PS) during the newborn period, or later in life following oral anticoagulant therapy with vitamin K antagonists, or of sepsis that may be associated with disseminated intravascular coagulation. Treatment consists of anticoagulants and PC concentrates during acute episodes. We report our experience in the diagnosis and management of pediatric PF. The medical records of the 6 children aged 2–16 years (median: 5 years) who presented with PF to our tertiary care center between 1996 and 2013 were studied. The thrombophilia workup revealed either the presence of congenital homozygous PC deficiency, prothrombotic polymorphisms (factor V Leiden and FIIG20210A heterozygosity), acquired PC/PS deficiency, or no discernible thrombophilia. The skin necrosis resolved following conservative fresh-frozen plasma/anticoagulant therapy in 2 cases, whereas 3 children required interventional plastic surgery. The sixth case, a 10-year-old child with severe PC deficiency, heterozygous factor V Leiden, and FIIG20210A, received recombinant activated PC. PF in childhood is rare and has multiple etiologies. Understanding of the variable pathogenesis and risk factors will facilitate diagnosis and appropriate clinical management.